PENGARUH BEBAN KERJA, KOMPETENSI SDM, DAN STRES KERJA TERHADAP KINERJA PEGAWAI BPBD KABUPATEN BOYOLALI - Maryanto Maryanto (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study focuses on evaluating the impact of workload, human resource competency, and job stress on employee performance within the Boyolali Regency Regional Disaster Management Agency (BPBD). To achieve the research objectives, a quantitative survey method was used. Data were obtained from questionnaires distributed to 56 employees as respondents. Multiple linear regression was used for data analysis with the aid of statistical software. The findings indicate that workload, human resource competency, and job stress collectively have a significant impact on employee performance. When examined separately, human resource competency exhibits a positive and significant effect on employee performance. Conversely, work stress and workload variables tend to exhibit a negative relationship, although the impact is considered insignificant. The findings indicate that human resource competency is the most dominant factor in improving employee performance within the Boyolali Regency BPBD. This study implies that improving the quality of human resources needs to be a priority in supporting effective disaster management.